Banking on youth : leveraging social investment in Trinidad & Tobago - Weber, Ron (1998)
Focuses on the pathbreaking efforts Services Volunteered for All (Servol) has patiently made during the last quarter century to bridge differences in class and ideology by forging private and public partnerships to build up the nation by investing in youth who have been given up for lost.